Health effects of exposure to static magnetic field − a review of literature - Marek Zmyślony; Piotr Politański (Nofer Institute of Occupational Medicine, 2019)
The authors discuss the effects of static magnetic field (SMF) exposure based on reviewed literature reports. The systematic review covered both research carried out directly with people as well as studies with animals. A review was carried out in terms of various potential effects: carcinogenic effects, reproductive and metabolic disorders or the influence of SMF on the nervous and circulatory system. The possible biophysical and biological effects of the SMF were also described. Med Pr. 2019;70(1):107-20